Peningkatan Literasi Melalui Pojok Baca Di Sekolah Dasar Negeri 3 Candikusuma - Edi Sutikno; Astri Widyaruli Anggraeni (STIKes Ibnu Sina Ajibarang, 2024)
Reading corners are students' reading activities carried out in between lessons to read books that are available on the reading corner shelves. Reading corners can also be called mini libraries in the classroom. Reading corners in the classroom can later improve students' ability to read books. available on the reading corner shelves. This research used qualitative methods by observing students directly and then describing them in detail so that readers could understand them. Based on the research results with the reading corner, students increasingly read books on the shelves. books according to each student's favorites, as well as attracting students' interest in reading. The reading corner is well managed by teachers and students with the aim of being a source of enjoyable learning reading.